Myxoid chondrosarcoma of maxilla: A rare case report. Issue 3 (May 2016) - Ash, Hiralal; Shahi, Ajoy Kumar; Chatterjee, Kabita; Samaddar, Dipankar
Abstract: Chondrosarcomas are malignant tumors arising from cartilaginous tissues. Myxoid chondrosarcoma is rare histological variant of chondrosarcoma that usually occurs in limbs. Head and neck is an extremely rare site for this kind of tumor with very few cases reported till date. We hereby report a case of myxoid chondrosarcoma involving the maxilla of an adult patient.